1997
DOI: 10.12693/aphyspola.92.911
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interface-Induced Disorder on Classical and Quantum Conductivity of CdTe:IN Epitaxial Layers

Abstract: An influence of disorder originated from the substrate/layer interface on electrical properties of CdTe:In layers was investigated by means of the Hall effect and magnetoresistance measurements at low temperatures. An estimation of a scattering rate due to interface-induced disorder is given. Characteristic features of a magnetic field dependence of magnetoresistance are explained by an influence of quantum interference of scattered electron waves both in the hopping and the free electron conductivity regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The possibility of observing the bolometric effect in [26] was connected with a small activation energy E of the conductivity in the samples investigated. The magnetoresistance measurements [14] showed that the hopping conductivity at liquid helium temperatures is characterized by E ≈ 1 meV, which means that even a very small increase of the lattice temperature can lead to observable conductivity changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of observing the bolometric effect in [26] was connected with a small activation energy E of the conductivity in the samples investigated. The magnetoresistance measurements [14] showed that the hopping conductivity at liquid helium temperatures is characterized by E ≈ 1 meV, which means that even a very small increase of the lattice temperature can lead to observable conductivity changes.…”
Section: Discussionmentioning
confidence: 99%
“…A further decrease of d b to 0.5 μm (sample A) makes the resistance of the sample too high for carrying out Hall effect measurements, as it is also in the case of sample C. At liquid helium temperatures, samples A, B and C were insulating. Magnetotransport studies showed that hopping is the appropriate mechanism of conductivity at low temperatures for sample D [14]. This indicates that the In concentration was smaller than the one corresponding to the Mott transition.…”
Section: Samples and Experimentsmentioning
confidence: 96%